Reaksi Pasar Modal terhadap Peritiwa Pengeboman Gereja di Surabaya - Cindy Agustina; Hadi Sumarsono; Edi Santoso (ASSET: Jurnal Manajemen dan Bisnis, 2020)
This study aims to examine the extent of the capital market reaction in the form of cumulative abnormal returns and cumulative trading volume activity from the bombing of the Church in Surabaya 13 May 2018 both in 3 Manufacturing Sectors and as a whole Manufacturing Companies. This study involved 97 Manufacturing companies listed on the IDX. The results showed that there was a significant difference between cumulative abnormal return 2 days before and 2 days after the bombing of the Church in Surabaya May 13, 2018 in the Miscellaneous Industry Sector and Basic and Chemical Industries, while the Consumer Goods Sector there was no significant cumulative abnormal return difference. The results also showed that there was a significant difference between cumulative trading volume activity 2 days before and 2 days after the bombing of the Church in Surabaya May 13, 2018 in the Consumer Goods Sector and the Basic and Chemical Industry Sector, while in the Various Industry Sector there was no difference in cumulative trading significant volume of activity. Meanwhile, the overall Manufacturing Company results showed that there was a significant difference between cumulative abnormal return and cumulative trading volume activity 2 days before and 2 days after the bombing of the Church in Surabaya 13 May 2018.